ANALISIS KADAR FENOLIK FRAKSI ETIL ASETAT DAUN PETAI CINA (Leucaena leucocephala) (Lam.) de Wit) SECARA SPEKTROFOTOMETRI Uv-Vis - Sari, Intan Purnama; Abidin, Zainal; Maryam, St (Jurnal Ilmiah As-Syifaa, 2020)
Traditionally, river tamarind leaves (Leucaena leucocephala (Lam.) De Wit.) can be used as medicine for injuries, swollen, diarrhea and also as antiseptic. The river tamarind leaves contains several main compounds such as alkaloids, saponins, flavonoids, phenols, mimosine, lectin, protein, oil, calcium, phosphorus, iron, vitamin A and vitamin B. The research aimed to determine the phenolic levels found in the ethyl acetate fraction of the leaves. The extraction was done by maceration method using ethanol 96% then fractionated with ethyl acetate solvent. The obtained fraction was analysed by UV-Vis spectrophotometry method at the maximum wavelength of 761 nm using gallic acid as a standard. Based on the qualitative test, river tamarind leaves positively contained phenolic. The phenolic compound contained in the ethyl acetate fraction was 0.176 mgGAE/g in that every gram of ethyl acetate fraction had phenolic of 0.176 mg equivalent to garlic acid.